2013
DOI: 10.1242/jeb.075911
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous locomotion and prey sensing in the leech

Abstract: SUMMARYThe medicinal leech, Hirudo verbana, is an aquatic predator that utilizes water waves to locate its prey. However, to reach their prey, the leeches must move within the same water that they are using to sense prey. This requires that they either move ballistically towards a pre-determined prey location or that they account for their self-movement and continually track prey. We found that leeches do not localize prey ballistically. Instead, they require continual sensory information to track their prey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…A previous study determined that leeches orient toward stimuli during crawling bouts [32]. While at first glance two orientation behaviors may seem redundant, it is possible that they have fundamentally different but cooperative functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study determined that leeches orient toward stimuli during crawling bouts [32]. While at first glance two orientation behaviors may seem redundant, it is possible that they have fundamentally different but cooperative functions.…”
Section: Discussionmentioning
confidence: 99%
“…This foot was placed such that it lay flat on the surface of the water when at rest. This stimulator created waves in the testing arena containing the leech [32].…”
Section: Methodsmentioning
confidence: 99%
“…Leeches also use the visible spectrum to orient while swimming, and they respond to shadows, or brief, bright flashes (Kretz et al, 1976). In addition, leeches orient to moving bars of visible light when hungry Carlton and McVean, 1993), and a recent set of elegant experiments have shown that leeches use frequency-modulated (moving bars) visible light in combination with tactile vibration (both of which are related to water disturbances) to orient and locate potential prey (Harley et al, 2011;Harley et al, 2013). Thus, it might be suggested that hirudiniid leeches are not particularly averse to visible light, and under some conditions may use it as an appetitive cue.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, leeches in the genus Hirudo are only modestly negatively phototactic when tested with artificial sources of visible light (Mann, 1962). This negative phototaxis to visible light is further reduced by feeding status, such that hungry leeches are somewhat positively phototactic, and have been shown to orient toward moving bars of light associated with water waves that might be produced by potential prey (Carlton and McVean, 1993;Dickinson and Lent, 1984;Harley et al, 2011;Harley et al, 2013). Although there have been a number of studies on the visual system of leeches showing sensitivity to visible wavelengths (Kretz et al, 1976;Laverack, 1969;Walz, 1982), as well as studies characterizing some of the interneuronal targets of photoreceptors within the central nervous system (Laverack, 1969;Peterson, 1984b;Peterson, 1985a;Peterson, 1985b), there has been no report of leeches detecting or responding to UVR.…”
mentioning
confidence: 99%
“…Behaviorally, they can use visual cues, mechanical cues, or a combination of the two to infer the presence of water waves and their direction of propagation (Dickinson and Lent, 1984;Carlton and McVean, 1993;Harley et al, 2011Harley et al, , 2013. Little has been known about processing of visual information in the leech, and less about processing of information relating to water movement.…”
Section: Discussionmentioning
confidence: 99%